EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN KECERDASAN EMOSIONAL SISWA - Fadil Maiseptian; Marjohan -; Yarmis - (Universitas Sultan Ageng Tirtayasa, 2017)
Emotional intelligence that has not developed can lead to aggressive behavior. The objective of study was to increase students' emotional intelligence after attending group guidance services. The research method used the Quantitative design of Quasi-Experiment with Time Series Design. Research subjects 10 students of class XI MAN 1 Padang selected with Purposive Sampling technique. Instruments used in the scale of emotional intelligence and data analysis using Wilcoxon Signed Rank Test. The results of the analysis stated that there were significant differences in pretest 1, 2, 3 scores with posttest 1, 2, 3 students' emotional intelligence after following group guidance service. Keyword: Group Guidance, Emotional Intelligence